Assessment of glucose effectiveness from short IVGTT in individuals with different degrees of glucose tolerance - Morettini, Micaela; Di Nardo, Francesco; Burattini, Laura; Fioretti, Sandro; Göbl, Christian; Kautzky-Willer, Alexandra; Pacini, Giovanni; Tura, Andrea (Acta diabetologica, 2018)
Aims Minimal model analysis of intravenous glucose tolerance test (IVGTT) data represents the reference method to assess insulin sensitivity ( S I ) and glucose effectiveness ( S G ) that quantify the insulin-dependent and insulin-independent processes of glucose disappearance, respectively. However, test duration (3 h) and need for modeling expertise limit the applicability of this method. Aim of this study was providing a simple predictor of S G applicable to short test (1 h), as previously done with S I . Methods Three groups of subjects reflecting different glucose tolerance degrees underwent a 3 h IVGTT: subjects with normal glucose tolerance (NGT, n = 164), with defective glucose regulation (DGR, n = 191), and with type 2 diabetes (T2D, n = 39). Minimal model analysis provided reference S G and its components at zero (GEZI) and basal (BIE) insulin. The simple predictor CS G (calculated S G ) was described by the formula CS G = α 0 + α 1 × K G / G peak , being K G the glucose disappearance rate (between 10 and 50 min) and G peak the maximum of the glucose curve during the test; α 0 and α 1 coefficients were provided by linear regression analysis. Results CS G and S G showed a markedly significant relationship in the whole dataset ( r = 0.72, p < 0.0001) and in the single groups ( r = 0.70 in NGT, r = 0.71 in DGR and r = 0.70 in T2D, p < 0.0001 for all); α 1 × K G / G peak was significantly related to GEZI ( r ≥ 0.60). Conclusions The interest for insulin-independent glucose disappearance is increasing, due to the recent availability of SGLT2 pharmacological agents, lowering glycemic levels without requiring insulin action. This study proposes a reliable predictor of S G based on IVGTT lasting 1 h only, and not requiring mathematical modeling skills.